Early ileocaecal resection versus biologics therapy for localized Crohn disease: A systematic review and meta‐analysis - Sara Bravin; Ana L. R. S. Menegat; Brenda L. R. S. Menegat; Omar Kasimieh; Henrique Wiederkehr (Colorectal Disease, 2026)
Abstract Aim Early ileocaecal resection has recently emerged as a feasible alternative to biologics in patients with localized Crohn's disease unresponsive to standard therapy. However, early resection is not widely implemented in clinical settings, and data on its comparison to biologics therapy are limited. Methods We searched PubMed, Scopus and Cochrane for randomized clinical trials (RCTs) and observational studies comparing early ileocaecal resection to biologics therapy in patients with localized Crohn's disease. Risk ratio (RR) was calculated for pooled outcomes; a p ‐value of < 0.05 was considered statistically significant. Results We included 1,644 patients from one RCT and two cohort studies, where 799 patients were treated with a surgery‐first approach (48.8%). In the biologics group, patients were mainly treated with infliximab or adalimumab. Fewer patients in the resection group required additional surgery beyond the allocated treatment compared to patients treated with biologics therapy (RR 0.09; 95% CI 0.03–0.24; p = 0.01). There was no statistically significant difference between groups regarding the need to escalate treatment to the other arm's therapy. In two studies, at final follow‐up, nearly half of the resection group (315/650, 48%) were off medication without further treatment, whereas all patients treated with biologics first required ongoing medical therapy or surgery. Conclusion In patients with localized predominantly inflammatory ileocaecal Crohn's disease, who are naïve to biologics therapy, early resection may reduce the need for subsequent treatment. These findings should be interpreted with caution due to the limited evidence base and the low to very low certainty of evidence highlighted by GRADE assessment.